Economic evaluation of Medically Assisted Reproduction: An educational overview of methods and applications for healthcare professionals. (December 2022) - Luyten, Jeroen; Connolly, Mark P.; Verbeke, Evelyn; Buhler, Klaus; Scotland, Graham; Lispi, Monica; Revelli, Alberto; Borget, Isabelle; Cedrin-Durnerin, Isabelle; D'Hooghe, Thomas
Abstract: Economic evaluations of the value-for-money of Medically Assisted Reproduction (MAR) interventions are increasingly important due to growing pressure on healthcare budgets. Although such evaluations are commonplace in the published literature, the number/methodological complexity of different evaluations available, and the challenges specific to MAR interventions, can complicate the interpretation of such analyses for fertility treatments. This article aims to serve as an educational resource and provide context on the design/interpretation of economic analyses for MAR interventions. Several areas are relevant for first-line providers and decision makers: scope of analysis, comparator used, perspective/time horizon considered, outcomes used to measure success, and how results from cost-effectiveness studies can be summarised and used in clinical practice. We aim to help clinicians better understand the strengths/weaknesses of economic analyses, to enable the best use of the evidence in practice, so resources available for MAR interventions can provide maximum value to patients and society. Highlights: This educational resource provides context on economic analyses for MAR treatment. Several factors can obstruct clear interpretation of economic analyses for MAR. These include the stakeholder/decision-maker, scope of analysis and comparator. The perspective/time horizon and outcome to measure success also need to be considered. Greater appreciation of these is essential to improve current methodologies.